2018
DOI: 10.1556/066.2018.47.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization and anti-ageing activity of Gastrodia elata blume polysaccharide

Abstract: Gastrodia elata Blume polysaccharide (GEP) was extracted and then chemically characterised. Its antioxidant activity was evaluated in vitro and in vivo. The results of the in vitro investigation show that GEP consists of glucose with molecular weight of 875 185 Da and exhibits high hydroxyl radical scavenging, as well as 2,2-diphenyl-1picrylhydrazyl activity and reducing capacity. For antioxidant activity in vivo, D-galactose-induced-aged mice were orally administered with three different doses of GEP over a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…One study extracted GP by the hot water extraction method, and chemical characterization by UV spectrometer and HPLC, then detected its antioxidant activity in vitro and in vivo. The results showed that GP could effectively remove hydroxyl radicals and has a substantial reduction ability [ 66 ]. Oral GP can increase the activities of SOD and GSH-Px in aging mice induced by D-galactose.…”
Section: Antioxidant Activity Of Natural Polysaccharidesmentioning
confidence: 99%
“…One study extracted GP by the hot water extraction method, and chemical characterization by UV spectrometer and HPLC, then detected its antioxidant activity in vitro and in vivo. The results showed that GP could effectively remove hydroxyl radicals and has a substantial reduction ability [ 66 ]. Oral GP can increase the activities of SOD and GSH-Px in aging mice induced by D-galactose.…”
Section: Antioxidant Activity Of Natural Polysaccharidesmentioning
confidence: 99%
“…The merits of these methods are their compatibility with polysaccharides. Due to the fact the Sevag method is much milder than the others, G. elata aqueous extract is typically deproteinized using the Sevag method [23,41,54]. The enzyme method is another effective and alternative to the common methods to eliminate proteins.…”
Section: Acquisition Of G Elata Polysaccharidesmentioning
confidence: 99%
“…Using a refractive index detector, Chen et al reported that G. elata RGP-1a is composed of fructose and glucose in a ratio of 1:10.68, and G. elata RGP-1b is only composed of glucose [24]. Using a carbohydrate column and a pulsed amperometric detector, Zhu et al reported that the G. elata polysaccharide GEP is composed of glucose [54]. Through the use of ion chromatography to analyze the monosaccharide composition of G. elata polysaccharides, Li et al reported that the G. elata polysaccharide is composed of rhamnose, galactose, glucose, xylose, and mannose [65].…”
Section: Analysis Of G Elata Polysaccharidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The protection of this phytomedicine on human umbilical vein endothelial cells (HUVEC) involved in these bioactivities [28,29]. On the other hand, with many polyphenols including the gastrodin-type components mentioned above, GET exerted predominant antioxidant activity, which also played a crucial role in its efficacies and was related to many pharmacological bioactivities, such as protection on liver and kidney jury, antiaging, reducing cerebral ischemia/reperfusion injury, antihypertension, neuroprotection [30,31,32,33,34,35,36]. Hence, HUVEC protective and antioxidant properties could also be utilized to reflect GET quality.…”
Section: Introductionmentioning
confidence: 99%